Antifungal mechanism of slightly acidic electrolyzed water against Phomopsis longanae Chi, the major pathogen causing fruit spoilage in postharvest longans - Qingqing Liu; Fanling Chen; Qin Zheng; Yifen Lin; Ruiling Zhuo; Yen-Con Hung; Hetong Lin; Yihui Chen (Food Control, 2027)

Dopamine triggers TOR signaling cascade to drive biomass and astaxanthin hyperaccumulation in Haematococcus lacustris under coordinated salinity and gradient light stress - Shiyu Lin; Qingwei Wang; Raoqiong Che; Qingqing Li; Chunli Yu; Min Yang; Lifang Li; Penghua Gao; Ying Qi; Feiyan Huang; Xiang Wang; Yongteng Zhao; et al. (Bioresource Technology, 2026)

Mimosa-inspired dual-responsive flocculant with controllable hydrophobicity/hydrophilicity reconstruction for the purification of triclosan containing emulsified wastewater - Wei Chen; Junquan Wang; Mengyi Lin; Xinyang He; Peipei Li; Yisheng Chen; Jinning Zhang; Qingqing Guan; Huaili Zheng (Water Research, 2026)

Stage-dependent roles of Trichoderma longibrachiatum and manganese sulfate in humification and nitrogen conservation during chicken manure composting - Yuchen Yang; Shuzhen Fan; Dan Zhang; Pan Wu; Shuang Peng; Qingqing Hua; Beibei Zhou; Yiming Wang; Xiangui Lin (Bioresource Technology, 2026)

A near-infrared fluorescent probe activated by cysteine for imaging hyperglycemia-induced oxidative stress injury in the liver - Wenzheng Wei; Qingqing Ma; Ling Huang; Weiying Lin (Analytica Chimica Acta, 2026)

Nanoconfined iron-based catalysts activate peroxymonosulfate via electron transfer and radical pathways for efficient bisphenol A removal - Mingyu Sun; Qingqing Hao; Jingxingyu Wu; Chenye Fu; Long Lin; Guochun Lv; Shihuai Deng; Xiaohui Lu; Jiali Peng (Journal of Hazardous Materials, 2026)

Tailoring the enzymatic microenvironment in bifunctional macroporous resins: Synergizing interfacial activation and structural rigidity for process-intensified biocatalysis in extreme solvents - Qingqing Liu; Jiaxiang Du; Weihang Lin; Xuanling Zhang; Yi Hu; Binbin Nian (Chemical Engineering Journal, 2026)

Superphosphate-driven low-pH regime reduces greenhouse gas emissions during manure composting - Yuchen Yang; Huijie Li; Pan Wu; Shuang Peng; Qingqing Hua; Beibei Zhou; Yiming Wang; Xiangui Lin (Bioresource Technology, 2026)

Effects of artificial shelter types and densities on the growth performance, physiological activities, and coloration of the giant river prawn Macrobrachium rosenbergii cultured indoors - Qingqing Li; Yong Wei; Qifeng Lu; Huai Zhang; Li Lin (Aquaculture, 2026)

Westerly reorganization driven by orbital forcing: Late Miocene aridification in the Tarim Basin, Central Asia - Dong Wang; Qingqing Qiao; Chuang Xuan; Zhuangzhuang Lv; Sunyi Dong; Gangqiang Li; Long Ma; Yudong Chen; Zhanwei Lin; Zhongyin Gao (Global and Planetary Change, 2026)

Enhancing microalgal bioremediation and bioproduction with chemical additives: Mechanisms and strategic perspectives - Yongteng Zhao; Shiyu Lin; Qingqing Li; Feiyan Huang; Xiang Wang; Lei Zhang; Xuya Yu; Lei Yu (Algal Research, 2026)

Effects of faba beans ( Vicia faba L.) on the growth, amino and fatty acids compositions, flesh quality and oxidative stability of African catfish, Clarias gariepinus - Qingqing Li; Qifeng Lu; Huai Zhang; Li Lin; Huohong Lv; Xinyi Li (Journal of Fish Biology, 2026)
The African catfish, Clarias gariepinus , is a commercially vital fish that is cultured worldwide, but it often exhibits low‐quality flesh despite high production, which limits its market value. Consequently, there is increasing interest in identifying alternative feed ingredients that can improve flesh quality without severely compromising growth performance. Previous studies have shown that the inclusion of raw faba beans ( Vicia faba L.) in the diet can improve muscle quality in species like tilapia and grass carp by increasing muscle crisped, yet information on their effects in C. gariepinus remains limited. This study aimed to assess the impacts of 0% (Diet I, control group), 40% (Diet II), 50% (Diet III), 60% (Diet IV) and 70% (Diet V) dietary faba beans inclusion on growth performance, physiological parameters and muscle quality of C. gariepinus during 90 days of cultivation. Compared to the control group, C. gariepinus fed faba beans‐containing diets exhibited lower body weight, body weight gain rate (WGR) and specific growth rate (SGR), accompanied by a significant decline in glucose‐6‐phosphate dehydrogenase activity ( p C. gariepinus receiving faba bean‐supplemented diets exhibited a higher density of muscle fibres, broader gaps between fibres and reduced fibre diameter compared with the control group. Fish fed 50% and 60% faba bean diets exhibited significantly greater muscle hardness ( p p C. gariepinus ; however, inclusion levels must be carefully managed because of their adverse effects on growth.

Mechanistic insights into efficient phenol degradation mediated by anodic respiration in Acinetobacter sp. LA-1 - Binxin Liu; Jingyi Yu; Rongsheng Lin; Wendong Xian; Dan Luo; Li Chen; Jianxin Wang; Wenhui Wang; Qingqing Zhang; Peng Li (Journal of Hazardous Materials, 2026)

Genetic diversity of passion fruit germplasms analyzed by using start codon targeted (SCoT) markers - Jiaqi Zhang; Zhenjie Zhang; Yunqi Xu; Qingqing Zhu; Yulan Zhang; Zeyao Lin; Sihao Wu; Qiujin Lin; Li Jiang; Lijun Du; Zongqiang Shi; Xianqian Niu; et al. (Genetic Resources and Crop Evolution, 2026)

Effects of dietary phytic acid on growth, antioxidant status, hepatic metabolism, and immune-related gene expression in Nile tilapia (Oreochromis niloticus) - Huai Zhang; Qifeng Lu; Jianwen Deng; Li Lin; Qingqing Li (Fish Physiology and Biochemistry, 2026)

Slightly acidic electrolyzed water enhances fruit disease resistance in longans by activating phenylpropanoid and flavonoid pathways - Qingqing Liu; Shengtai Lin; Yuxin Wu; Zhongqi Fan; Ruiling Zhuo; Yifen Lin; Boqiang Li; Shiping Tian; Mengshi Lin; Hetong Lin; Yihui Chen (Postharvest Biology and Technology, 2026)

Modulating probiotic stability via diacylglycerol phase behavior in co-encapsulation systems: The role of solid fat content and melting properties - Ying Chen; Fuyou Zhang; Lin Zhang; Qingqing Xu (Food and Bioproducts Processing, 2026)

Genetic deletion of miR-200a/200b increases growth and feed conversion efficiency in yellow catfish - Xu Wang; Yan Xie; Qiaohong Lin; Yang Xiong; Ying Liu; Si Ge; Qiuen Tan; Zhipeng He; Youbo Jiang; Qingqing Han; Shuang Jin; Peipei Huang; et al. (Science China Life Sciences, 2026)

Development of Two Multienzyme Isothermal Rapid Amplification Techniques for the Rapid Visual Detection of Micropterus salmoides rhabdovirus - Qingyue Xu; Yiping Lin; Yixia Ma; Zhantian Liao; Tao Li; Shuai Wang; Chunguo Liu; Zhan Luo; Qingqing Song; Shun Zhou; Yunji Xiu (Journal of Fish Diseases, 2026)
Largemouth bass ( Micropterus salmoides ) is an important freshwater‐cultured species in China. M. salmoides rhabdovirus (MSRV) is a devastating pathogen that causes high mortality (exceeding 90% in acute outbreaks) in largemouth bass fry, posing a severe threat to the global largemouth bass aquaculture industry. To address the urgent demand for rapid, on‐site MSRV detection, two multienzyme isothermal rapid amplification (MIRA)‐derived methods—multienzyme isothermal rapid amplification with fluorescence detection (MIRA‐FLU) and multienzyme isothermal rapid amplification with lateral flow dipstick (MIRA‐LFD)—were established and optimized targeting the conserved nucleoprotein (N) gene of MSRV. The performance of both methods was systematically evaluated, and their practical applicability was verified using clinical samples collected from diseased fish farms. The results demonstrated that both methods exhibited high sensitivity, with a detection limit of 9 copies/μL for the standard plasmid. Both detection methods demonstrated high specificity and showed no cross‐reactivity with other common aquatic viruses, indicating their high specificity for MSRV detection. MIRA‐FLU completed amplification within 25 min at 42°C, while MIRA‐LFD achieved amplification within 12 min at 37°C. MIRA‐FLU is used for real‐time fluorescent quantitative detection, whereas MIRA‐LFD enables visual, instrument‐free reading via lateral flow test strips. In comparative analyses of clinical samples, the diagnostic results of MIRA‐FLU and MIRA‐LFD were compared with those of the standard conventional PCR test and showed nearly 100% consistency. Therefore, our MIRA‐FLU and MIRA‐LFD detection methods demonstrate excellent specificity and sensitivity, providing two simple, rapid and reliable approaches for large‐scale field surveys of MSRV in resource‐limited settings.

Application of ε-poly-L-lysine alleviates postharvest disease in fresh longans incurred by Phomopsis longanae Chi via regulating the metabolisms of reactive oxygen species and membrane lipids - Xiaoze Dai; Qingqing Liu; Junzheng Sun; Ruiling Zhuo; Yifen Lin; Mengshi Lin; Boqiang Li; Shiping Tian; Hetong Lin; Yihui Chen (Postharvest Biology and Technology, 2026)

High-frequency observation reveals the impacts of suspended sediment and hysteresis effect on water quality in soil erosion areas - Yongqiang Lin; Zhixiang Sun; Jiacheng Li; Jiayu Jiang; Qingqing Zuo; Tengyu Zhang; Kun An; Zhenyao Shen; Lei Chen (Journal of Hydrology, 2026)

Performance and microbial response of suspended carrier-enhanced MBR treating tungsten smelting ammonia-nitrogen wastewater - Duliang Huang; Lin Huang; Jinmao Ye; Yu Zhang; Qingqing Yang; Changming Zhong (Journal of Environmental Chemical Engineering, 2026)

Partial nitrification-denitrification strategies with different sludge sources and their impact on membrane fouling behavior - Duliang Huang; Qingqing Yang; Lin Huang; Jinmao Ye; Yu Zhang; Changming Zhong (Journal of Environmental Management, 2026)

Stabilization of oleogels using high internal-phase Pickering emulsions stabilized by myofibrillar proteins from large yellow croaker as a template: Effect of pH and transglutaminase - Zhongyang Ren; Qingqing Li; Min Lin; Yuan Zhao; Linfan Shi; Shuji Liu; Zhiyu Liu; Wuyin Weng (Food Chemistry, 2026)

Manure-driven antibiotic resistance in agroecosystems: Decadal evidence of accumulation dynamics and food chain transmission - Shuang Peng; Shaoying Xu; Beibei Zhou; Qingqing Hua; Pan Wu; Xiangui Lin; Yiming Wang (Journal of Hazardous Materials, 2026)

Chicken sternum cartilage protein-chelated calcium: enhance bone density in vivo and in vitro, with insights into chelation mechanism - Shikun Suo; Yanli Wang; Lihui Du; Maolin Tu; Kuo Dang; Jingyi Chen; Yi Lin; Yali Dang; Qingqing Li (Food Research International, 2026)

Integrated approach to uranium recovery and organic decomposition with electricity generation in a self-driven photoelectrochemical system - Qingqing Yang; Yi-Lin Liu; Haiyi Gong; Qingyan Zhang; Shuaishuai Guo; Qingyi Zeng (Journal of Environmental Sciences, 2026)

Flexible multi-parameter sensing platform using MoWS2-BP composite for environmental and physiological monitoring - Yu Qi; Long Yang; Zitong Kan; Qingqing Zhou; Biao Dong; Guodong Wei; Hongwei Song; Lin Xu (Chemical Engineering Journal, 2026)

Soil calcium ion enrichment associated with altered microbial functional gene networks in bamboo forest expansion - Yaoxing Wu; Huimin Tian; Jiahuan Guo; Yawen Shen; Qingqing Liu; Lin Yu; Zhiyin Tang; Yihang Jia; Gong Zhang; Jun Deng; Lianghua Qi (Applied Soil Ecology, 2026)

L-amino acids modulate biofilm formation, UV resistance, and insecticidal activity in Bacillus thuringiensis formulations: Mechanisms and optimization - Zixuan Wang; Yimeng Zhang; Junjun Chen; Qingqing Liu; Xueqin Luo; Qiuting Xu; Hongxin Su; Yanyan He; Fang Xiong; Shuang Lin; Tianpei Huang; Xiong Guan (Pesticide Biochemistry and Physiology, 2026)

The variability of phosphorus fractions and transport driven by rainfall at both plot and catchment scales - Zhixiang Sun; Lei Chen; Yu Pu; Yongqiang Lin; Qingqing Zuo; Jiayu Jiang; Tengyu Zhang; Kun An; Zhenyao Shen (Journal of Hydrology, 2026)

Large-eddy simulation of ammonia/coal co-combustion in a laboratory-scale burner using an extended flamelet/progress variable (FPV) model - Qingqing Xue; Jiangkuan Xing; Xinzhou Tang; Junjie Lin; Kun Luo; Jianren Fan (Fuel, 2026)

The glymphatic system in psychiatric disorders: a new perspective - Teng Gao; Zhe Wang; Serik Tabarak; Qingqing Yin; Lin Lu (Science Bulletin, 2025)

Engineering NK cell membrane-camouflaged copper-BODIPY nanoassembly to synergize dual-phototherapy and cuproptosis for enhanced antitumor immunity - Xuya Yu; Yushi Zhang; Zhuona Rong; Xueping Li; Lingpeng Luo; Lu Zhang; Liyu Sun; Yayue Liu; Wen Li; Lin Mei; Feng Lv; Xiaocong Pang; et al. (Chemical Engineering Journal, 2025)

Charcoal-derived hard carbon anodes with enhanced sodium storage performance for sodium-ion batteries - Shengchen Yang; Yan Li; Chun Chen; Hui Wang; Kaihang Wang; Qingqing Li; Ruize Dong; Manman Chen; Cai Zhao; Weiwei Xu; Lin Sun; Tao Zhang; et al. (Chemical Engineering Journal, 2025)

Comparison of growth performance and non‐specific immunity of Nile tilapia ( Oreochromis niloticus ) fed with non‐germinated and germinated faba bean - Xi Xie; Meiyan Chen; Qingqing Li; Ling Yang; Zhendong Qin; Lijuan Zhao; Shaowen Liang; Li Lin (Journal of Fish Biology, 2025)
Faba bean ( Vicia faba L.) has garnered interest from the aquatic feed industry as a plant‐based ingredient that may enhance muscle hardness and crispness in tilapia. However, faba beans contain numerous anti‐nutritional factors (ANFs) that could affect animal growth and health through their metabolic products. Germination effectively reduces the content of ANFs in faba beans; however, the effects of germinated faba beans on tilapia growth and non‐specific immunity remain unclear. In this study, the growth parameters, antioxidant activity, carbon metabolic enzyme activity and immune‐related gene expression profiles of tilapia fed with germinated faba beans (FB1 and FB5 groups) and non‐germinated faba beans (FB0 group) were compared. The FB1 and FB5 groups exhibited heavier body weight (514.39 ± 111.66 g and 546.87 ± 98.16 g) compared to the FB0 group (392.53 ± 78.34 g) on day 80 ( p interleukin‐1 beta ( IL‐1β ), C‐C motif chemokine ligand 3 ( CCL3 ) and tumour necrosis factor‐alpha ( TNF‐α ) were downregulated initially and then gradually upregulated by day 80. Expression of heat shock protein 70 ( Hsp70 ) upregulated in the FB1 and FB5 groups relative to that in normal tilapia (control). These findings suggest that incorporating faba beans into tilapia feed may reduce oxidative stress and modulate immune responses in tilapia cultures.

Mercapto-modified layered double hydroxide: High-efficiency emerging amendment for cadmium immobilization in cadmium-contaminated acidic and alkaline soil - Xusheng Gao; Xilin Chen; Yifei Shu; Kexin Chen; Ge Gao; Xiaomin Liu; Qingqing Huang; Lin Wang; Yuebing Sun; Yujie Zhao; Xuefeng Liang (Journal of Hazardous Materials, 2025)

Isolation, evolution, and biological characterization of non-virulent and non-drug-resistant Escherichia coli from porcine intestine - Bingming Ou; Biyang Xiao; Qingqing Li; Jiayi Wang; Xue Lin; Weinan Zhong; Huimin Zhu; Yufu Liu; Shaoting Li; Hongmei Zhang; Wenhua Liu; Minyu Zhang (Folia Microbiologica, 2025)

Seaweed polysaccharides as potential Prebiotics: Rationale, factors, Prebiotic activity manifestations, gut health mechanisms and extraintestinal impacts - Qianmin Lin; Li Zhong; Mei Zeng; Supaluck Kraithong; Xuewei Xia; Weiyang Kuang; Qingqing Wang; Riming Huang (Trends in Food Science & Technology, 2025)

Selectivity characteristics of immobilization effects of sulfhydryl grafted palygorskite on heavy metals in soils - Xilin Chen; Xusheng Gao; Yifei Shu; Xiaomin Liu; Qingqing Huang; Lin Wang; Yuebing Sun; Yujie Zhao; Xuefeng Liang (Science of The Total Environment, 2025)

A three-dimensional Pt@Ti₃C₂Tₓ-based smart platform for discrimination of hydrated ammonia in multi‐scenario environmental monitoring - Qingqing Zhou; Chencheng Hu; Yu Qi; Xiaoyi Tan; Jiaqi Yang; Zitong Kan; Long Yang; Biao Dong; Zhiyong Chang; Hongwei Song; Lin Xu (Journal of Hazardous Materials, 2025)

Preliminary investigation on the mechanism of electromagnetic coupling to reduce thawing loss of frozen beef - Chuan Yang; Yong Chen; Qingqing Li; Guangyu Wu; Hengxun Lin; Wei Jia; Chengjiang Liu; Chunhui Zhang; Xia Li (Food and Bioproducts Processing, 2025)

Theoretical and experimental investigation on mortar-sprayed corrugated steel pipe under parallel-plate loading condition - Zihao Zhu; Cong Zeng; Xuehao Wang; Qingqing Wu; Dongting Wang; Lin Hu; Baosong Ma; Peng Zhang (Tunnelling and Underground Space Technology, 2025)

Liquid metal modified all-nanofiber triboelectric nanogenerator for energy harvesting and multi-functional self-powered sensing - Long Yang; Wenbo Hu; Ruida Cao; Qingqing Zhou; Chencheng Hu; Biao Dong; Hongwei Song; Lin Xu (Chemical Engineering Journal, 2025)

Benzo(a)pyrene-loaded gypsum dust-induced apoptosis of human bronchial epithelial cells through the Ahr signaling pathway - Yujun Wang; Juan Song; Qingqing Lin; Zhenzhen Lv; Faqin Dong; Jianjun Deng (Molecular & Cellular Toxicology, 2025)

A redox-modulating coating with multi-enzyme activity on engineered nanoparticles: An effective strategy for enhancing the control of plant bacterial diseases - Zhenghao Ding; Liwei Liu; Qingqing Song; Lin Chen; Guangdi Wang; Hong Li; Xinxin Tuo; Zhibing Wu; Xiang Zhou; Song Yang (Chemical Engineering Journal, 2025)

Impacts of changes in PM2.5 concentrations and their major components on blood pressure during pregnancy - Peiyao Chen; Wenjie He; Yan Jin; Xueting Liu; Qiannan Wei; Jianling Shen; Qingqing Wang; Li Wen; Lijie Wang; Qing Wei; Qiansheng Hu; Weiwei Lin (Journal of Hazardous Materials, 2025)

A vertical reverse zoning in the Kunshan W-Mo-Cu deposit, South China: Insights from mineral paragenesis, zircon geochemistry and S-Pb-O isotopes - Qingqing Yin; Juxing Tang; Qiuming Pei; Inna Safonova; Xinkui Xiang; Jingjing Dai; Aorigele Zhou; Bin Lin; Yumin Xu; Zhendong Yu; Jinling Xie; Ruihua Lin; et al. (Gondwana Research, 2025)

Composite antimicrobial films activated by essential oil pickering emulsions: Preparation, characterization and application in pork preservation - Lin Liu; Tanghui Liu; Guihong Li; Qingqing Tan; Anjun Tang; TingTing Wen; Ziming Li; Hai Chi; Hongrui Chen; Jie Tang; Xingzhong Zhang (Food Bioscience, 2025)

Faraday cage-type photocurrent polarity switching photoelectrochemical sensing platform for highly selective and sensitive detection of Vibrio parahaemolyticus - Qingqing Zhang; Tingting Zhai; Yuxin Guo; Yifan Weng; Nan Zhou; Han Lin; Hao Tan; Kangning Lu; Yiyi Zhou (Food Chemistry, 2025)

Converting static to Dynamic: Biomimetic Ultra-Sensitive Wide-Range flexible pressure sensor inspired by the Contact-Regulation process of scorpion pectines - Junqiu Zhang; Jiachao Wu; Lili Liu; Xiangbo Gu; Xueping Zhang; Xueyang Li; Zijian Shi; Yu Chen; Jiqi Gao; Junfeng Zhang; Tao Sun; Honglie Song; et al. (Chemical Engineering Journal, 2025)

Development and validation of a prediction model for the depressive symptom risk in commercial airline pilots - Jie Zhang; Xuhua Chen; Lin Zhang; Haodong Qi; Erliang Zhang; Minzhi Chen; Yiran Wang; Yunfei Li; Yan Chen; Qingqing Duan; Feng Shi; Linlin Wang; et al. (EPMA Journal, 2025)

Microglia Sing the Prelude of Neuroinflammation-Associated Depression - Qingqing Li; Ying Xie; Jinyi Lin; Miaomiao Li; Ziyan Gu; Tianli Xin; Yang Zhang; Qixia Lu; Yihui Guo; Yanhong Xing; Wuyang Wang (Molecular Neurobiology, 2025)

Bimetallic active sites with tailored d-bands boost multistep sulfur redox reactions for enhanced lithium-sulfur battery performance - Wei Wang; Jianguo Si; Liguo Yue; Weicai Zhang; Qingqing Chen; Haoliang Huang; Fei Lin; Yang Zhao; Sheng Meng; Lifeng Liu (Chemical Engineering Journal, 2025)

Tannic acid reduced the growth performance, antioxidant, and immune functions of the Nile tilapia (Oreochromis niloticus) - Junhui Liu; Xingqian Zhang; Qifeng Lu; Huai Zhang; Li Lin; Qingqing Li (Aquaculture, 2025)

Changes in freezing parameters and temperature distribution of beef induced by AC electric field: Alleviation on freezing damage and myowater loss - Hengxun Lin; Jing Wang; Prince Chisoro; Guangyu Wu; Songsong Zhao; Xiaojia Hu; Chuan Yang; Yunhe Liu; Wei Jia; Qingqing Li; Chunhui Zhang; Christophe Blecker; et al. (Journal of Food Engineering, 2025)

Melatonin treatment maintains the quality properties and storability of carambola fruit by modulating energy metabolism - Ting Hu; Shaojie Zheng; Qingqing Liu; Meiling Li; Jingyuan Chen; Huili Zhang; Mengshi Lin; Hetong Lin; Yihui Chen (Food Chemistry, 2025)

Neutrophil Membrane Nanovesicles Alleviate the Renal Function Indicators in Acute Kidney Injury Caused by Septic Rats - Junhao Pan; Feifei Shao; Xiaorong Xiao; Xin Ke; Zhihui Guan; Hui Lin; Qingqing Yan; Xinyao Xiang; Jinming Luo (Cell Biochemistry and Biophysics, 2025)

Recent advancements in antibiotics removal by bio-electrochemical systems (BESs): From mechanisms to application of emerging combined systems - Jing Tang; Zijun Li; Xinxin Xiao; Baicheng Liu; Wei Huang; Qingqing Xie; Chenrui Lan; Shuai Luo; Lin Tang (Water Research, 2025)

Paddy-upland rotation combined with manure application: An optimal strategy for enhancing soil multifunctionality - Dan Zhang; Jianbin Sun; Shuang Peng; Yiming Wang; Qingqing Hua; Pan Wu; Xiangui Lin (Journal of Environmental Management, 2025)

Regulatory effects and mechanism of different selenium species on cadmium accumulation in Triticum aestivum L. (microbial response, gene expression and element accumulation) - Xuerong Di; Rui Jing; Xu Qin; Xuefeng Liang; Lin Wang; Yingming Xu; Yuebing Sun; Qingqing Huang (Environmental Research, 2025)

Effects of tank color on body color change, astaxanthin content, and antioxidant capacity of the giant river prawn (Macrobrachium rosenbergii) - Junhui Liu; Zeling Luo; Xinyan Chen; Li Lin; Qingqing Li (Aquaculture International, 2025)

Occurrence and human exposure risk of antibiotic resistance genes in tillage soils of dryland regions: A case study of northern Ningxia Plain, China - Jianbin Sun; Dan Zhang; Shuang Peng; Xiaoqian Yang; Qingqing Hua; Wei Wang; Yiming Wang; Xiangui Lin (Journal of Hazardous Materials, 2024)

Sub-millimeter scale 3D integration strategy enables ultrahigh-density and ultralow-crosstalk flexible tactile sensor array for robotic e-skin application - Shaoxiong Hu; Rui Wang; Wei Zhu; Yue Huang; Ying Li; Yuchen Yang; Qingqing Zhang; Yuedong Yan; Chen Lin; Yuan Deng (Chemical Engineering Journal, 2024)

Exploring the role of static magnetic field in supercooling storage from the viewpoint of meat quality and microbial community - Yong Chen; Hengxun Lin; Yiping Yang; Liye Cui; Prince Chisoro; Chuan Yang; Guangyu Wu; Qingqing Li; Jingjun Li; Chunhui Zhang; Xia Li (Food Research International, 2024)

Electric fields as effective strategies for enhancing quality attributes of meat in cold chain logistics: A review - Hengxun Lin; Guangyu Wu; Xiaojia Hu; Prince Chisoro; Chuan Yang; Qingqing Li; Christophe Blecker; Xia Li; Chunhui Zhang (Food Research International, 2024)

Inorganic Carbon Pools and Their Drivers in Grassland and Desert Soils - Longwei Dong; Jinzhi Ran; Jiali Luo; Lin Bai; Ying Sun; Muhammad Aqeel; Yahui Zhang; Xiaoting Wang; Qiajun Du; Junlan Xiong; Haiyang Gong; Qingqing Hou; et al. (Global Change Biology, 2024)
Inorganic carbon is an important component of soil carbon stocks, exerting a profound influence on climate change and ecosystem functioning. Drylands account for approximately 80% of the global soil inorganic carbon (SIC) pool within the top 200 cm. Despite its paramount importance, the components of SIC and their contributions to CO 2 fluxes have been largely overlooked, resulting in notable gaps in understanding its distribution, composition, and responses to environmental factors across ecosystems, especially in deserts and temperate grasslands. Utilizing a dataset of 6011 samples from 173 sites across 224 million hectares, the data revealed that deserts and grasslands in northwestern China contain 20 ± 2.5 and 5 ± 1.3 petagrams of SIC in the top 100 cm, representing 5.5 and 0.76 times the corresponding soil organic carbon stock, respectively. Pedogenic carbonates (PIC), formed by the dissolution and re‐precipitation of carbonates, dominated in grasslands, accounting for 60% of SIC with an area‐weighted density of 3.4 ± 0.4 kg C m −2 at 0–100 cm depth, while lithogenic carbonates (LIC), inherited from soil parent materials, prevailed in deserts, constituting 55% of SIC with an area‐weighted density of 7.1 ± 1.0 kg C m −2 . Soil parent materials and elevation determined the SIC stocks by regulating the formation and loss of LIC in deserts, whereas natural acidification, mainly induced by rhizosphere processes including cation uptake and H + release as well as precipitation, reduced SIC (mainly by PIC) in grasslands. Overall, the massive SIC pool underscores its irreplaceable role in maintaining the total carbon pool in drylands. This study sheds light on LIC and PIC and highlights the critical impact of natural acidification on SIC loss in grasslands.

Comparative transcriptome and metabolome reveal the role of acidic electrolyzed oxidizing water in improving postharvest disease resistance of longan fruit - Zhongqi Fan; Ling Fang; Qingqing Liu; Hetong Lin; Mengshi Lin; Yifen Lin; Hui Wang; Yen-Con Hung; Yihui Chen (Food Chemistry, 2024)

Associations of Plasma Lipidomic Profiles with Uric Acid and Hyperuricemia Risk in Middle-Aged and Elderly Chinese - Wanhui Kang; Xinming Xu; Xiaowei Yang; Qingqing Wu; Shuning Li; Keran Gao; Rong Zeng; Liang Sun; Xu Lin (Phenomics, 2024)
Little is known about the links of disturbed lipid metabolism with hyperuricemia (HUA). We aimed to investigate the associations of lipidomic profiles with uric acid (UA)/HUA and their modifying factors in middle-aged and elderly Chinese. A total of 350 lipids were quantified in 2247 community-based Chinese aged 50–70 years by high-coverage targeted lipidomics. HUA was defined by plasma UA > 420 μmol/L in men or > 360 μmol/L in women. The prevalence of HUA in this population was 10.4%. After multivariable adjustment including BMI and lifestyle, 123 lipids were significantly associated with UA, predominantly glycerolipids (GLs) and glycerophospholipids (GPs). Specifically, diacylglycerol [DAG (16:0/22:5), DAG (16:0/22:6), DAG (18:1/20:5), DAG (18:1/22:6)], phosphatidylcholine [PC (16:0/20:5)), and triacylglycerol (TAG (53:0)] were the most significant lipid signatures positively associated with HUA risk, while lysophosphatidylcholine (LPC (20:2)) was inversely associated with HUA risk ( p < 0.05). Network analysis also showed a positive association between TAGs/PCs/DAGs contained module and HUA risk ( p < 0.01). Notably, HUA-related lipids were associated with de novo lipogenesis fatty acids, especially 16:1n-7 (Spearman correlation coefficients = 0.32–0.41, p < 0.001). Reduced rank regression showed that increased aquatic products intake was correlated to elevated HUA risk and HUA-associated lipids; while high dairy consumption was correlated with low level of HUA-associated lipids (|factor loadings| ≥ 0.2). Moreover, mediation analyses suggested that the lipid-HUA associations were partially mediated by retinol-binding protein 4 (RBP4, mediation proportion 5–14%), an adipokine linked with dyslipidemia and insulin resistance. In conclusion, disturbed specific metabolisms of GLs and GPs were associated with high prevalent HUA, partially mediated by RBP4 and/or influenced by certain dietary factors.

A near-infrared fluorescent probe for differentiating cancer cells from normal cells and early diagnosis of liver cirrhosis - Chenyuan Long; Qingqing Ma; Ling Huang; Weiying Lin (Analytica Chimica Acta, 2024)

Critical insights into the Hormesis of antibiotic resistome in saline soil: Implications from salinity regulation - Jianbin Sun; Dan Zhang; Shuang Peng; Xiaoqian Yang; Qingqing Hua; Wei Wang; Yiming Wang; Xiangui Lin (Journal of Hazardous Materials, 2024)

The role and transcriptomic mechanism of cell wall in the mutual antagonized effects between selenium nanoparticles and cadmium in wheat - Xuerong Di; Rui Jing; Xu Qin; Xuefeng Liang; Lin Wang; Yingming Xu; Yuebing Sun; Qingqing Huang (Journal of Hazardous Materials, 2024)

Combined multi-level context aggregation and attention mechanism method for photovoltaic panel extraction from high resolution remote sensing images - Qingqing Qi; Jinghao Zhao; Lu Lin; Xiaoqing Zhang; Yajun Tian (International Journal of Remote Sensing, 2024)

A short-term of starvation improved the antioxidant activity and quality of African catfish (Clarias gariepinus) - Fanbin Zhan; Qingqing Li; Huiwen Feng; Ruikang Lin; Weiming Liang; Li Lin; Zhendong Qin (Fish Physiology and Biochemistry, 2024)

Clostridium butyricum upregulates GPR109A/AMPK/PGC-1α and ameliorates acute pancreatitis-associated intestinal barrier injury in mice - Guiqing Deng; Biyan Wen; Lin Jia; Jiaxin Liu; Qingqing Yan (Archives of Microbiology, 2024)

Characteristics of sub-micron aerosols above the urban canopy in Beijing during warm seasons - Qingqing Wang; Wei Du; Wei Zhou; Yingjie Zhang; Conghui Xie; Jian Zhao; Weiqi Xu; Guiqian Tang; Pingqing Fu; Zifa Wang; Yele Sun; Lin Peng (Science of The Total Environment, 2024)

Comprehensive assessment of the microbial community structure in a typical lead–zinc mine soil - Taotao Zeng; Haichao Sha; Qingqing Xie; Yue Lu; Haidu Nong; Liangqin Wang; Lin Tang (Environmental Science and Pollution Research, 2024)

Ecological characteristics of sugar beet plant and rhizosphere soil in response to high boron stress: A study of the remediation potential - Jialu Huo; Baiquan Song; Xiaochen Lin; Muhammad Riaz; Xiaoyu Zhao; Shangxuan Liu; Qingqing She (Journal of Environmental Management, 2024)

An accurate model for the solubilities of anhydrite in H2O–NaCl solutions at temperatures up to 1073 K, pressures up to 14,000 bar, and mole fractions of NaCl up to 0.3 - Qingqing Wang; Lin Zhang; Jiawen Hu; Xunli Shi (Chemical Geology, 2024)

Effects of myricetin and quercetin on ticagrelor metabolism and the underlying mechanism - Jing Wang; Yingying Hu; Qingqing Li; Ya-nan Liu; Jingjing Lin; Ren-ai Xu (Chemico-Biological Interactions, 2024)

Dosage and exposure time effects of two micro(nono)plastics on arbuscular mycorrhizal fungal diversity in two farmland soils planted with pepper (Capsicum annuum L.) - Baiping He; Zihao Liu; Xin Wang; Minghui Li; Xiangui Lin; Qingqing Xiao; Junli Hu (Science of The Total Environment, 2024)

Transcriptome and ultrastructural analysis revealed the mechanism of Mercapto-palygorskite on reducing Cd content in wheat - Yu Zhang; Yingming Xu; Qingqing Huang; Xuefeng Liang; Yuebing Sun; Lin Wang (Journal of Hazardous Materials, 2024)

Identifying the function of the PI3K‐AKT pathway during the pathogenic infection of Macrobrachium rosenbergii - Fanbin Zhan; Shichun Zhou; Fei Shi; Qingqing Li; Li Lin; Zhendong Qin (Journal of Fish Diseases, 2024)
The phosphoinositide‐3‐kinase/protein kinase b (PI3K‐Akt) pathway is a signalling pathway based on protein phosphorylation and can be activated by a wide range of factors. To investigate the function of the PI3K‐AKT signalling pathway in antibacterial immunity, we analysed the gene expression level of three key factors ( PI3K , AKT and FoxO ) and innate immune factors in immune tissues at different time points after Vibrio parahaemolyticus and Staphylococcus aureus infection. Tissues analysis showed that PI3K , AKT , and FoxO were expressed at high levels in the intestinal, hemocytes and hepatopancreas. Moreover, the expression levels of PI3K , AKT and FoxO can be regulated postinfection by different pathogens. In hemocytes and the intestine, V . parahaemolyticus infection was found to regulate the levels of PI3K , AKT , and FoxO more rapidly; however, an S . aureus infection regulated the levels of these factors more rapidly in the hepatopancreas and gills. Analysis showed that V . parahaemolyticus and S . aureus infection caused changes in the gene expression level of crustin , caspase 3 and NF‐κB . Therefore, PI3K‐AKT regulates the downstream immune pathway differentially in different immune tissues and participates in the regulation of cell apoptosis and the inflammatory response by activating caspase and NF‐κB, respectively, following infection with V . parahaemolyticus and S . aureus .

Use of a new Tibetan Plateau network for permafrost to characterize satellite-based products errors: An application to soil moisture and freeze/thaw - Jingyao Zheng; Tianjie Zhao; Haishen Lü; Defu Zou; Nemesio Rodriguez-Fernandez; Arnaud Mialon; Philippe Richaume; Jianshe Xiao; Jun Ma; Lei Fan; Peilin Song; Yonghua Zhu; et al. (Remote Sensing of Environment, 2024)

Activation of peroxymonosulfate by Cu–Ni–Fe layered double oxides for degradation of butyl 4-hydroxybenzoate: Synergistic effect of oxygen vacancy and Cu(I) - Huiwang Dai; Jingyi Zhu; Fanxu Meng; Daohui Lin; Wenjun Zhou; Dingjiang Chen; Ming Zhang; Qingqing Wang (Chemosphere, 2023)

The variability in CYP3A4 activity determines the metabolic kinetic characteristics of ketamine - Mengfang Li; Qingqing Li; Dan Lin; Xiang Zheng; Lehao Jin; Jianping Cai; Guoxin Hu; Jianchang Qian (Toxicology, 2023)

Transcriptome analysis reveals the molecular mechanism of different forms of selenium in reducing cadmium uptake and accumulation in wheat seedlings - Xuerong Di; Rui Jing; Xu Qin; Yihua Wei; Xuefeng Liang; Lin Wang; Yingming Xu; Yuebing Sun; Qingqing Huang (Chemosphere, 2023)

Effect of national COVID-19 control measures on water quality in China using an improved dual difference-in-differences method - Jian Zhao; Qingqing Liu; Jing Bai; Haixia Liu; Lin Ding (Science of The Total Environment, 2023)

Role of antenatal anxiety in the relationship between maternal exposure to nitrogen dioxide and small for gestational age: A birth cohort study - Qiannan Wei; Weiwei Lin; Hedi Zhang; Yuming Lai; Shuling Zhuang; Zhenyan Han; Qingqing Wang; Lijie Wang; Wenzhuo Li; Li Wen; Hongying Hou; Qiansheng Hu (Science of The Total Environment, 2023)

Acidic electrolyzed oxidizing water delayed the breakdown occurrence in pulp of fresh longan by regulating the metabolisms of respiratory and energy - Qingqing Liu; Huilin Xie; Yihui Chen; Mengshi Lin; Yen-Con Hung; Hui Wang; Zhongqi Fan; Yifen Lin; Hetong Lin (Postharvest Biology and Technology, 2023)

Exposure to three herbicide mixtures influenced maize root-associated microbial community structure, function and the network complexity - Qingyun Ma; Qingqing Li; Jie Wang; Rebecca E. Parales; Lin Li; Zhiyong Ruan (Environmental Pollution, 2023)

Effect of the inoculation of Phanerochaete chrysosporium on nitrogen migration and organic matter conversion during electrolytic manganese residue composting - Xiangyu Peng; Ming Yan; Qingqing Xie; Lan Gao; Xiaojuan Pu; Yukui Fu; Hanwen Liu; Min Cheng; Piao Xu; Danlian Huang; Lin Tang (Bioresource Technology, 2023)

Assessing the suitability of municipal sewage sludge and coconut bran as breeding medium for Oryza sativa L. seedlings and developing a standardized substrate - Linyi Lin; Jiemin Qin; Yu Zhang; Jiaxin Yin; Genmao Guo; Muhammad Amjad Khan; Yin Liu; Quan Liu; Qingqing Wang; Kenlin Chang; Ondřej Mašek; Junfeng Wang; et al. (Journal of Environmental Management, 2023)

The effects of prenatal PM2.5 oxidative potential exposure on feto-placental vascular resistance and fetal weight: A repeated-measures study - Weiwei Lin; Yuming Lai; Shuling Zhuang; Qiannan Wei; Hedi Zhang; Qiansheng Hu; Peng Cheng; Manman Zhang; Yuhong Zhai; Qingqing Wang; Zhenyan Han; Hongying Hou (Environmental Research, 2023)

Effects of faba beans (Vicia faba L.) on growth performance, textural quality and physiological indices of tilapia (Oreochromis niloticus) - Qingqing Li; Yao Huang; Xingqian Zhang; Zhendong Qin; Cuiyun Zou; Xiaohong Tan; Xi Xie; Shaowen Liang; Li Lin (Aquaculture, 2023)

Ionomic analysis reveals the mechanism of mercaptosilane-modified palygorskite on reducing Cd transport from soil to wheat - Yu Zhang; Yingming Xu; Xuefeng Liang; Lin Wang; Yuebing Sun; Qingqing Huang; Xu Qin (Environmental Science and Pollution Research, 2023)

Comparison of bacterial and fungal communities structure and dynamics during chicken manure and pig manure composting - Dan Zhang; Jianbin Sun; Danqing Wang; Shuang Peng; Yiming Wang; Xiangui Lin; Xiaoqian Yang; Qingqing Hua; Pan Wu (Environmental Science and Pollution Research, 2023)

Effect of Ca–modified biochar coupling with low–Cd accumulation maize cultivars on remediation of Cd contaminated soils and microbial community composition - Tong Sun; Wenhao Yang; Yingming Xu; Lin Wang; Xuefeng Liang; Qingqing Huang; Yuebing Sun (Soil and Tillage Research, 2023)

Transcriptome analysis of Macrobrachium rosenbergii hemocytes in response to Staphylococcus aureus infection - Fanbin Zhan; Shichun Zhou; Fei Shi; Qingqing Li; Li Lin; Zhendong Qin (Fish & Shellfish Immunology, 2023)

A visible and near-infrared light dual-responsive PEC immunosensor for archaeological silk microtrace detection based on in situ growth of Ag2S on ZnO-MXene nanocomposites - Qingqing Zhou; Yong Liu; Lin Wang; Kun Wang; Haodong Chen; Hailing Zheng; Yang Zhou; Zhiwen Hu; Zhiqin Peng; Junmin Wan; Bing Wang (Chemical Engineering Journal, 2023)

The identification of dual active routes for highly efficient furfural oxidation reaction coupling with hydrogen production over Re modulated Co(OH)2/CC - Qingqing Pang; Chenxiao Feng; Xizheng Fan; Kaihang Sun; Kun Xiang; Lin Dong; Shufang Zhao; Young Dok Kim; Qiaoyun Liu; Zhongyi Liu; Zhikun Peng (Chemical Engineering Journal, 2023)

Effects of drug-drug interactions and CYP3A4 variants on alectinib metabolism - Ya-nan Liu; Jie Chen; Jing Wang; Qingqing Li; Guo-xin Hu; Jian-ping Cai; Guanyang Lin; Ren-ai Xu (Archives of Toxicology, 2023)

Sodium alginate/chitosan-based intelligent bilayer film with antimicrobial activity for pork preservation and freshness monitoring - Shenghui Cao; Shuo Wang; Qingqing Wang; Gang Lin; Baolong Niu; Ruijie Guo; Hong Yan; Huifang Wang (Food Control, 2023)

Characterization analysis of TLR5a and TLR5b immune response after different bacterial infection in grass carp (Ctenopharyngodon idella) - Fanbin Zhan; Yanan Li; Fei Shi; Zhijie Lu; Minxuan Yang; Qingqing Li; Li Lin; Zhendong Qin (Fish & Shellfish Immunology, 2023)

Characterization of a new chlorimuron-ethyl-degrading strain Cedecea sp. LAM2020 and biodegradation pathway revealed by multiomics analysis - Qingyun Ma; Xiaoyan Han; Jinlong Song; Jie Wang; Qingqing Li; Rebecca E. Parales; Lin Li; Zhiyong Ruan (Journal of Hazardous Materials, 2023)

Transcriptome analysis of Macrobrachium rosenbergii hemocytes reveals in-depth insights into the immune response to Vibrio parahaemolyticus infection - Fanbin Zhan; Yanan Li; Fei Shi; Zhijie Lu; Minxuan Yang; Qingqing Li; Li Lin; Zhendong Qin (Fish & Shellfish Immunology, 2023)

Comparison of growth, and non-specific immune of crisp and ordinary tilapia (Oreochromis niloticus) - Qingqing Li; Yao Huang; Xi Xie; Xiaoqian Zhai; Meiyan Chen; Dejin Liang; Ming Cao; Shaowen Liang; Li Lin (Aquaculture, 2023)

Effects of mercapto-palygorskite application on cadmium accumulation of soil aggregates at different depths in Cd-contaminated alkaline farmland - Yu Zhang; Yanli Li; Yingming Xu; Qingqing Huang; Guohong Sun; Xu Qin; Lin Wang (Environmental Research, 2023)

Successful treatment of ceftazidime/avibactam combined with aztreonam in the NDM-producing Klebsiella pneumoniae bloodstream and intestinal infections in a NK/T lymphoma patient with agranulocytosis during autologous hematopoietic stem cell transplantation: a case report - Shiyi Liu; Qingqing Lin; Lizhi Ouyang; Chengjie Zhou; Huajun Wang (European Journal of Clinical Microbiology & Infectious Diseases, 2022)
New Delhi metallo-beta-lactamase (NDM)-producing Klebsiella pneumoniae is increasingly reported worldwide. Clinicians face significant challenges in the treatment of this multidrug-resistant bacterium. The combination of ceftazidime/avibactam (CAZ/AVI) and aztreonam (ATM) is currently probably the most effective strategy for the treatment of such infection. We described a patient diagnosed with NK/T cell lymphoma who underwent autologous hematopoietic stem cell transplantation (ASCT) in the hematology department. The patient developed severe infection after ASCT. Blood and stool cultures showed carbapenem-resistant K. pneumoniae . Blood sample was detected as NDM-producing K. pneumoniae . We successfully treated this infection with CAZ/AVI and ATM.

Plasma Lipidomic Subclasses and Risk of Hypertension in Middle-Aged and Elderly Chinese - Zhenhua Niu; Qingqing Wu; Yaogan Luo; Di Wang; He Zheng; Yanpu Wu; Xiaowei Yang; Rong Zeng; Liang Sun; Xu Lin (Phenomics, 2022)

Calcium Homeostasis in Parkinson’s Disease: From Pathology to Treatment - Jingxian Zhang; Qingqing Shen; Yue Ma; Lin Liu; Wenting Jia; Leilei Chen; Junxia Xie (Neuroscience Bulletin, 2022)

Water demand in watershed forecasting using a hybrid model based on autoregressive moving average and deep neural networks - Guangze Liu; Mingkang Yuan; Xudong Chen; Xiaokun Lin; Qingqing Jiang (Environmental Science and Pollution Research, 2022)

The mechanism and application of bidirectional extracellular electron transport in the field of energy and environment - Qingqing Xie; Yue Lu; Lin Tang; Guangming Zeng; Zhaohui Yang; Changzheng Fan; Jingjing Wang; Siavash Atashgahi (Critical Reviews in Environmental Science and Technology, 2021)

Protective effect of Bombyx mori gloverin on intestinal epithelial cells exposure to enterotoxigenic E. coli - Qian Lin; Qingqing Fu; Guoqi Su; Daiwen Chen; Bing Yu; Yuheng Luo; Ping Zheng; Xiangbing Mao; Zhiqing Huang; Jie Yu; Junqiu Luo; Hui Yan; et al. (Brazilian Journal of Microbiology, 2021)

Prospect of utilizing coal mine drainage sludge as an iron source for value-creating applications - Rifat Anwar; Musfique Ahmed; Payton Seats; Qingqing Huang; Lian-Shin Lin (Reviews in Environmental Science and Bio/Technology, 2021)

Human β-Defensin 118 Attenuates Escherichia coli K88–Induced Inflammation and Intestinal Injury in Mice - Qian Lin; Qingqing Fu; Xiang Li; Yuheng Luo; Junqiu Luo; Daiwen Chen; Xiangbing Mao; Bing Yu; Ping Zheng; Zhiqing Huang; Jie Yu; Hui Yan; et al. (Probiotics and Antimicrobial Proteins, 2021)

Generation of a porcine reproductive and respiratory syndrome virus expressing a marker gene inserted between ORF4 and ORF5a - Yuxu Wang; Wei He; Qingqing Li; Xin Xie; Nian Qin; Hao Wang; Jiabin Huang; Siyuan Lin; Kang Ouyang; Ying Chen; Weijian Huang; Zuzhang Wei (Archives of Virology, 2020)

Somatic Mutations Confer Severe Peripheral Neuropathy in POEMS Syndrome-Associated Multicentric Castleman Disease - Qingqing Lin; Juying Wei; Jiejing Qian; Liangshun You; Wenbin Qian (Neuroscience Bulletin, 2020)

Effects of chicken manure application on cadmium and arsenic accumulation in rice grains under different water conditions - Yiyun Liu; Yingming Xu; Qingqing Huang; Xu Qin; Lijie Zhao; Xuefeng Liang; Lin Wang; Yuebing Sun (Environmental Science and Pollution Research, 2019)

Effects of water and organic manure coupling on the immobilization of cadmium by sepiolite - Yiyun Liu; Yingming Xu; Xu Qin; Lijie Zhao; Qingqing Huang; Lin Wang (Journal of Soils and Sediments, 2019)

Iron nanoparticles in situ encapsulated in lignin-derived hydrochar as an effective catalyst for phenol removal - Qingqing Ma; Lin Cui; Shuang Zhou; Yan Li; Weijie Shi; Shiyun Ai (Environmental Science and Pollution Research, 2018)

Remediation mechanisms of mercapto-grafted palygorskite for cadmium pollutant in paddy soil - Xuefeng Liang; Xu Qin; Qingqing Huang; Rong Huang; Xiuling Yin; Yanming Cai; Lin Wang; Yuebing Sun; Yingming Xu (Environmental Science and Pollution Research, 2017)

A20 reduces lipid storage and inflammation in hypertrophic adipocytes via p38 and Akt signaling - Luoyan Ai; Xiaohan Wang; Zhiwei Chen; Qing Lin; Dazhi Su; Qingqing Xu; Changwei Wu; Xiaoke Jiang; Antao Xu; Zhuping Fan (Molecular and Cellular Biochemistry, 2016)

Two-year stability of immobilization effect of sepiolite on Cd contaminants in paddy soil - Xuefeng Liang; Yi Xu; Yingming Xu; Pengchao Wang; Lin Wang; Yuebing Sun; Qingqing Huang; Rong Huang (Environmental Science and Pollution Research, 2016)

Response of CaCl2-extractable heavy metals, polychlorinated biphenyls, and microbial communities to biochar amendment in naturally contaminated soils - Wei Liu; Shutao Wang; Peng Lin; Hanwen Sun; Juan Hou; Qingqing Zuo; Rong Huo (Journal of Soils and Sediments, 2016)

Decreasing Transmembrane Segment Length Greatly Decreases Perfringolysin O Pore Size - Qingqing Lin; Tong Wang; Huilin Li; Erwin London (The Journal of Membrane Biology, 2015)

Endogenous Salicylic Acid Levels and Signaling Positively Regulate Arabidopsis Response to Polyethylene Glycol-Simulated Drought Stress - Qingqing He; Shiyang Zhao; Qunfei Ma; Yiyan Zhang; Linli Huang; Guangzhe Li; Lin Hao (Journal of Plant Growth Regulation, 2014)

Arabidopsis ein2-1 and npr1-1 Response to Al Stress - Yiyan Zhang; Qingqing He; Shiyang Zhao; Linli Huang; Lin Hao (Bulletin of Environmental Contamination and Toxicology, 2014)

Pulmonary Toxicity in Mice Following Exposure to Cerium Chloride - Jie Hong; Xiaohong Yu; Xiaoyu Pan; Xiaoyang Zhao; Lei Sheng; Xuezi Sang; Anan Lin; Chi Zhang; Yue Zhao; Suxin Gui; Qingqing Sun; Ling Wang; et al. (Biological Trace Element Research, 2014)

Detection of trends in precipitation extremes in Zhejiang, east China - Ye Tian; Yue-Ping Xu; M. J. Booij; Shengji Lin; Qingqing Zhang; Zhanghua Lou (Theoretical and Applied Climatology, 2012)